The Effect of Social Media on Customer Loyalty and Company Performance of Insurance Industry - Delafrooz, Narges; Zendehdel, Marzieh; Fathipoor, Maryam (International Journal of Economics and Financial Issues, 2017)
Due to vast changes in the marketing world, traditional methods are not enough to meet companies’ needs. On the other hand, changing customer communication channels and fragmentation of this communication from supplier to consumer has reduced more and more the customers’ trust and belief. Social media provides the partners of insurance companies (sale representatives) with an opportunity for creating fast and effective communication with customers. Statistical population of the research consists of distribution channel of Iran and Asia insurance companies in three levels of central offices (supplier), representatives of these companies and customers as consumers. Sampling method is a combination of random cluster sampling for central offices of Iran and Asia insurance companies, using Morgan table for sale representatives and Cochran’s formula for unlimited population for customers. Data was gathered using field method and by questionnaires and was analysed using single-variable hierarchical regression and using SPSS software. Results indicate that social media usage has a chain relation in the supply channel of Iran and Asia insurance companies and creation of this chain relation will make customers loyal to sale representatives of insurance companies and will improve representatives’ performance and brand sale of Iran and Asia insurance companies. Keywords: Social media, loyalty, contagion theory, performance, brand reputation, customer interaction, insurance companies. JEL Classifications: L1, L82, M